2016
DOI: 10.3823/2101
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure Assessment Of Patients In Palliative Home Care

Abstract: This study aims to examine the family structure of patients in palliative home care in the light of the Calgary Family Assessment Model (CFAM). This is a qualitative research, conducted in the residences of patients enrolled in the Palliative Care Unit and Pain Treatment (PCUP) of a university hospital located in Recife/Pernambuco, Brazil, in the period from May to July 2014. The sample consisted of five patients enrolled in the PCUP and five family caregivers. Data collection was performed through an intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In this study, all participants reported having a religion; however, this aspect was not significantly associated with the comfort of the caregiver. Faith is a way of finding strength to face the disease, even with the impossibility of healing 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all participants reported having a religion; however, this aspect was not significantly associated with the comfort of the caregiver. Faith is a way of finding strength to face the disease, even with the impossibility of healing 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Families are the basic components of all societies, founded on parental duty, mutually supportive relationships, emotional commitment, and oriented to protection and social bonding 119 . In recent decades, the structure and organization of the family has been transformed, 120,121 with the concept of chosen family 122 adopting a family‐centred model of care and healthcare provision 123 . The care provided by family members or friends is an important factor throughout the HF trajectory, but particularly so, in the advanced stages of the illness (online supplementary material, Case Study 3).…”
Section: Impact Of Culture On Communication and The Role Of The Familymentioning
confidence: 99%